The Oxford handbook of depression and comorbidity - Richards, C. Steven; O'Hara, Michael W. (Oxford library of psychology., 2014)
Depression is frequently associated with other psychiatric disorders, chronic health problems, and distressed close relationships. This comorbidity between depression and other disorders and problems is important. Furthermore, there has been a large increase in research on depressive comorbidity. Therefore, a book of 37 state-of-the-art reviews by experts will be helpful to teachers, researchers, practitioners, developers of relevant policies, and students in these areas. The comorbidity of depression with other psychiatric disorders is addressed in chapters focusing on panic disorder, post-traumatic stress disorder, social anxiety disorder, generalized anxiety disorder, alcohol-use disorders, eating disorders, conduct disorder, personality disorders, sexual dysfunctions, schizophrenia, suicide, and bipolar disorder. The comorbidity of depression and chronic health problems is addressed in chapters focusing on cardiovascular disease, cancer, pain, obesity, sleep disorders, multiple sclerosis, acquired immune deficiency syndrome, kidney disease, dementia, and women’s health. The comorbidity of depression and distressed close relationships is addressed in chapters on intimate relationships, family relationships, and perinatal depression. There are also chapters on diagnostic issues, theory and constructs, models of comorbidity between depression and anxiety, assessment strategies, multidisciplinary treatments, community interventions, treatment in ethnic minority groups, psychosocial interventions for depressed cancer patients, and cognitive therapy for comorbid depression. Finally, in an effort to integrate the material, there are introduction, big picture, and epilogue chapters. The 37 chapters in this book reflect a scholarly and evidence-based perspective on depressive comorbidity. Moreover, the chapters address a wide array of relevant issues, including etiology, assessment, diagnosis, course, theory, research, practice, treatment, and clinical guidelines. In summary, this edited book includes 37 chapters on depression and comorbidity, and thereby provides a comprehensive, scholarly, and empirically-based compendium of reviews on this topic.